2014
DOI: 10.1007/s40140-014-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Resuscitation

Abstract: Hypotensive resuscitation is a component of damage control resuscitation, the evolving approach to resuscitation in severely injured trauma patients. Resuscitation strategies used in treating severely injured trauma patients have changed dramatically over the last 20 years. The purpose of this review is to examine the current literature pertaining to hypotensive resuscitation, explore its use in damage control resuscitation, and examine blood pressure management in the setting of severe trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Permissive hypotension may have a survival benefit. [ 13 ] In our study, the volume of polygeline was administered based on the patient's condition and was well tolerated by all patients without increased bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Permissive hypotension may have a survival benefit. [ 13 ] In our study, the volume of polygeline was administered based on the patient's condition and was well tolerated by all patients without increased bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic shock is the major cause of potentially preventable death after accidental injuries and accounts for over 40% of deaths within the first 24 h in trauma patients [2]. Adequate fluid resuscitation to compensate for intravascular volume deficits and to support organ perfusion is an essential cornerstone in the treatment of patients with traumatic-hemorrhagic shock [3]. High-volume fluid resuscitation, however, carries the well-recognized risk of fluid overload, which can lead to third-spacing of fluids into tissues, edema formation, coagulopathy, abdominal compartment syndrome, or acute lung injury, and significantly contributes to mortality and morbidity in critically ill patients [46].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, rabbit mean arterial pressure decreased to 40 to 50 mm Hg in the current study, suggesting the rabbits were subjected to severe shock conditions. Notably, transfusion of allogeneic RBCs or HbVs increased the pressure to 50 to 55 mm Hg, which is generally recommended in hypotensive management . Shrestha et al demonstrated that damage control resuscitation increases successful nonoperative management rates and survival after severe blunt liver injury.…”
Section: Discussionmentioning
confidence: 99%